DIFFUSION-WEIGHTED IMAGING IN MR MAMMOGRAPHY AS AN ALTERNATIVE TO BIOPSY IN THE EVALUATION OF INTERMEDIATE NON-MASS BREAST LESIONS - Mohamed Awad, Fatma (International Journal of Research -GRANTHAALAYAH, 2019)
Background: Dynamic contrast-enhanced MRI is a sensitive tool for the diagnosis of breast cancer, however, its value is limited in cases of non-mass enhancement. Diffusion-weighted imaging (DWI) is promising in the diagnosis of non-mass breast lesions. Purpose: The aim of this study is to determine the value of diffusion-weighted imaging in the evaluation of intermediate non-mass breast lesions, as an alternative to biopsy. Materials and Methods: Thirty-three female patients between the ages of 38-56 years (mean age, 45 years) with non-mass lesions on MR mammography were included in this study. The lowest ADC values were obtained for the non-mass breast lesions. MR-guided core-needle biopsies were performed for 20 patients, while the other patients who refused biopsy, had yearly mammography and ultrasound every six months for two years. They also had at least one follow up MR mammography within the two years’ interval. Results: This study included 33 non-mass breast lesions detected on MR mammography. The lesion siz¬es ranged from 0.2 to 1.4 cm. The morphological characteristics of the lesions and their signal intensity curves on dynamic MR Mammography were recorded. For differentiation of benign and malignant lesions, a threshold ADC value of 1.03×10–3 mm2/s was used. The ADC values for all the lesions ranged from 1.3 x 10–3 mm2/s to 2.6 x 10–3 mm2/s. Conclusion: Diffusion-weighted imaging is effective in the evaluation of intermediate non-mass breast lesions on MR mammography and can be used as an alternative to biopsy.